Fast-atom Bombardment Mass Spectrometry for Mapping of Endogenous Methylated Purine Bases in Urine Extracts - Porcelli, Brunetta; Muraca, Lucia Filomena; Frosi, Barbara; Marinello, Enrico; Vernillo, Remo; De Martino, Antonio; Catinella, Silvia; Traldi, Pietro (Rapid communications in mass spectrometry, 1997)
Fast‐atom bombardment (FAB) mass spectrometry, linked with tandem mass spectrometry (MS/MS), was employed for the identification of methylated purine bases in four urinary extracts of healthy subjects and fourteen urinary extracts of patients bearing colorectal tumors. In order to obtain an easy structural identification of the species present in urinary extracts, the MS/MS spectra of MH+ species of twenty nine diagnostically relevant purine bases were studied. Even if definitive quantitative data cannot be obtained by this approach, FAB mass spectra of urine extracts lead to a readily reproducible mapping of endogenous purine bases, allowing a distinction between healthy and sick subjects. Bases such as 9‐ethyladenine, N6‐2‐isopentenyladenine and N6‐benzyladenine were detected only in urine samples of colorectal tumor bearing patients. The detection in urine of compounds such as 7‐methylguanine and 1‐methylguanine, and their increase in the urine of colorectal tumor bearing patients, has been justified either by a more rapid turnover of nucleic acids in tumor tissue or by an increase in the extent of their methylation. The obtained results indicate that the method can be employed for diagnostic purposes. © 1997 John Wiley & Sons, Ltd.